Macroinvertebrates composition as determinants of larval abundance in the dragonfly Miathyria marcella in tropical wetlands - M.I. Moreno Pallares; M.A. Bonilla Gómez; G.H. Guillot Monroy; A.C. Torregroza-Espinosa (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Odonate larvae play an important role in macroinvertebrate trophic networks and are excellent proxies for wetland quality. However, despite their ecological importance, research on odonates and how they interact with their environment is scarce. This study aims to assess macroinvertebrate composition as determinants of larval abundance in Miathyria marcella (Odonata: Anizoptera: Libellulidae).METHODS: 29 samples were collected from six wetlands with different hydrological influence using standardized invertebrate sampling techniques in the Department of Atlántico, northern Colombia. Standardized invertebrate sampling techniques were used in 29 sampling points. Obtained data were used to analyze invertebrate abundance and a non-parametric multidimensional scaling analysis was applied. In addition, a correlation analysis was conducted between macroinvertebrate composition and Miathyria  marcella larval abundance.FINDINGS: A total of 2586 larvae, and 12925 individual macroinvertebrates were collected, distributed in 25 orders and 58 families. The most abundant orders were Neotaenioglossa (26 percent), Odonata (15 percent) Calanoida (10 percent) and Diptera (8 percent). Heatmap and scaling analysis indicated different macroinvertebrate compositions in the sampled wetlands. A high positive correlation between Miathyria marcella and the orders Odonata (R2 = 0.84, p-value ≤ 0.05), Coleoptera (R2 = 0.52, p-value ≤ 0.05), Basommatophora (R2 = 0.60, p-value ≤ 0.05) and Hemiptera (R2 = 0.50, p-value ≤ 0.05).CONCLUSION: The results suggest that the abundance of Miathyria marcella responds to the accompanying macroinvertebrates, the composition of which depends on the type of hydrological influence. Approaches focused on the relationships between macroinvertebrate taxa are important conservation tools for biodiversity assessment. Results from this study will serve as a baseline to propose monitoring and follow-up strategies on the environmental sustainability in wetlands in this region.